Optimum polarization configuration of planar circular patch MIMO antenna - Rina Pudji Astuti; Eva Lucky Wijaya; Trasma Yunita; Harfan Hian Ryanu (JURNAL INFOTEL, 2022)
Multiple Input Multiple Output (MIMO) is a key technology that plays an important role in achieving the 5G requirement due to its capability to increase channel capacity. However, the increase of channel capacity is influenced by several aspects such as mutual coupling. Many methods are done to decrease the mutual coupling effect such as polarization arrangement of the MIMO antennas. This study on the polarization arrangement of a circular patch MIMO antenna at 3.5 GHz was performed. Four elements of the MIMO antenna are arranged with several polarization configurations both in Co-Polarization and Cross-Polarization. Both simulation and measurement results showed that MIMO with Co-Polarization has a slightly wider bandwidth equal to 295.25 MHz compared to Cross-Polarization with a bandwidth of 274.63 MHz, due to better return loss performed by the former. However, from the mutual coupling perspective, it is observed that MIMO with Cross-Polarization can reduce the mutual coupling from -17.6676dB into -22.462 dB compared to Co-Polarization with the same element distance.